Profit Shifting Through Transfer Pricing: A Systematic Review on Its Influence on Corporate Tax Aggressiveness - Mediaty, Mediaty; Usman, Asri; Ashar, Muhammad; Fitriani, Fitriani (DINASTI RESEARCH, 2025)
This article presents a systematic review of profit shifting practices through transfer pricing mechanisms and their impact on corporate tax aggressiveness. Transfer pricing, which involves setting prices for transactions between companies within a multinational business group, is often used to shift profits from high-tax jurisdictions to low-tax jurisdictions. This study uses the Systematic Literature Review (SLR) methodology. The results show that common strategies used include price manipulation of intangible assets, utilization of tax havens, thin capitalization, and price engineering of goods and services between group entities. Weak and non-standardized transfer pricing policies encourage increased corporate tax aggressiveness, especially in jurisdictions with limited fiscal oversight. On the other hand, the effectiveness of tax authorities in controlling profit shifting practices is greatly influenced by institutional capacity, cross-country data transparency, and international tax policy harmonization. These findings emphasize the importance of reforming global tax policies that are fairer, more transparent, and more integrated. This study is expected to provide theoretical and practical contributions for policymakers in formulating effective transfer pricing regulations to combat tax avoidance by multinational companies.